Dorothy Clay Nance and husband Henry Nance in a tobacco field, 1959. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 7-28-59 p.1.
Dorothy Clay Nance and husband Henry Nance in a tobacco field, 1959.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth